Situation of Khmer Minority in Vietnam. Policy of the Vietnamese Authorities and Durability of the Khmer Tradition - Zaręba, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2023)
This article aims to analyze the current socio-economic situation of the Khmer minority in Vietnam and to present the evolution of the Vietnamese government’s policy towards this ethnic group since the period of division to present days. In order to realize this goal, the following research questions were asked: 1) What is the status of the Khmer community in Vietnam regarding social and economic level?; 2) Has the Khmer minority developed a sense of a strong, separate identity?; 3) What is the policy of the Vietnamese authorities towards the Khmercommunity? The analysis aims to verify the hypothesis that declarations of the Vietnamese government regarding the implementation of a policy respecting cultural diversity, improving living conditions and material situation of the Khmer people are not fulfilled. There are still many neglected spheres, and the Khmer people suffer discrimination, maintaining a strong sense of national identity by cultivating Khmer traditions and customs.